Model Pembelajaran Aqidah dan Akhlak Integratif-Inklusif Berbasis Teknologi Digital dalam Membangun Sikap Moderasi Beragama Peserta Didik - Aisyah Puan Maharani; Muhammad Misbah; Muhammad Royhan Assaiq (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study explores the transformation of Aqidah and Akhlak learning through an integrative–inclusive learning model based on digital technology in fostering students’ religious moderation attitudes in the digital era. The study is motivated by the tendency of Islamic Religious Education learning to remain normative and conceptual, thus limiting its ability to address contemporary socio-religious challenges, particularly issues of plurality and digital culture development. The informants in this study were Islamic Religious Education teachers and secondary-level students who were directly involved in the implementation of digital technology-based learning. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings indicate that the integration of digital technology transformed Aqidah and Akhlak learning into a more reflective, dialogical, participatory, and contextual learning process. The utilization of digital media such as interactive videos, online discussion forums, and technology-based collaborative projects increased students’ engagement while fostering tolerance, respect for differences, and awareness of religious moderation both within the school environment and in broader digital spaces. The novelty of this study lies in the development of an integrative–inclusive Aqidah and Akhlak learning model that positions digital technology not merely as a learning medium, but also as a pedagogical space for internalizing the values of religious moderation in a global context.   Keywords: Aqidah and Akhlak Learning, Integrative–Inclusive, Digital Technology, Religious Moderation, Islamic Religious Education